Pengaruh Lokasi Fasilitas Dan Kualitas Pelayanan Terhadap Keputusan Pasien Memilih Jasa Rawat Inap Di Rumah Sakit Khusus Bedah Budi Kasih Majalengka - Dewi, Nyoman Nila; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study was conducted to determine the influence of location, facilities, and service quality on the decision to choose inpatients at RSBK Majalengka. The method used in this study is a quantitative approach. Data collection techniques with sampling techniques used in this study are purposive sampling and the use of this data by distributing questionnaires. The analysis used is descriptive and verifiative, multiple linear analysis, determination analysis, hypothesis test using t test (partial) and f test (simultaneous). Data was obtained and processed using SPSS (Statistical Package for The Social Science) software version 26.0. The results of this study show that facilities and service quality have a positive influence on the decision to choose patients. However, location did not positively affect the decision to choose patients. Simultaneously, location, facilities, and service quality have a significant influence on the decision to choose RSBK Majalengka.